Frontispiece: lewis superacids: classifications, candidates, and applications - Greb, Lutz (Chemistry - a European journal, 2018)
Lewis acidity scaling methods and the properties and applications of the strongest known Lewis (super)acids are covered in this contribution, which shall encourage the search for new Lewis superacids and promote their application in non-specialized laboratories. For more information, see the Minireview by L. Greb on page?17881?ff.